Airborne observations of aerosol extinction by in situ and remote‐sensing techniques: Evaluation of particle hygroscopicity. Issue 2 (18th January 2013) - Ziemba, Luke D.; Lee Thornhill, K.; Ferrare, Rich; Barrick, John; Beyersdorf, Andreas J.; Chen, Gao; Crumeyrolle, Suzanne N.; Hair, John; Hostetler, Chris; Hudgins, Charlie; Obland, Michael; Rogers, Raymond; et al.
<x xml:space="preserve">Abstract</x> [1] Extensive profiling of aerosol optical, chemical, and microphysical properties was performed in the Washington DC/Baltimore MD region in July 2011 during NASA DISCOVER‐AQ. In situ extinction coefficient (σext, in‐situ) measurements were made aboard the NASA P3‐B aircraft coincident with remote‐sensing observations by the High‐Spectral Resolution Lidar (HSRL; σext, HSRL) aboard the NASA UC‐12 aircraft. A statistical comparison revealed good agreement within instrumental uncertainty (σext, in‐situ = 1.1 σext, HSRL − 3.2 Mm−1, r2 = 0.88) and demonstrated the robust nature of hygroscopicity measurements (f(RH)) necessary to correct observations at dry relative humidity (RH) to ambient conditions. The average liquid‐water contribution to ambient visible‐light extinction was as much as 43% in this urban region. f(RH) values were observed to vary significantly from 1.1 to 2.1 on a day‐to‐day basis suggesting influence from both local and transported sources. Results emphasize the importance of accounting for the RH dependence of optical‐ and mass‐based aerosol air‐quality measurements (e.g., of PM2.5), especially in relation to satellite and remote‐sensing retrievals.